Proposed interior design of batik exclusive boutique retail at Lot PT27/29 Lorong Lahat Mines 1, 31500 Bandar Lahat Mines Perak Darul Ridzuan Shamshie Enterprise / Mohammad Sufian Jusoh - Jusoh, Mohammad Sufian (Faculty of Architecture, Planning and Surveying, 2012)
A final year student pursuing a diploma course in interior architecture is requisite to organize a final year project. All the design must be connected to the project that has been decided. Before making the design, major aspect must be considered to get the information. The research, case study, design schematic and the planning have to be done to ensure that the client will have a good reaction to our design. Because of that, the organization work must been done perfectly starting from the design development until the end of the project. Proposed new interior design scheme of Batik Exclusive Boutique Retail for Shamshie Enterprise is one of the compensation to the client to establish their product in entire Malaysia because Batik only famous at Kelantan and Terengganu. Shamshie Enterprise also want to support the industries batik craft treasury in Malaysia. According to the objective and the issue, a space planning must be suitable with the design concept and the images. So, to realize the design into the space is a difficult way because it has the procedures that must be followed. The planning that has been produced and the ideas that wanted to be applied into the space must be linked to the concept and the images. So, the good design is produced with the concept, the images into the design axis and followed by the development of the ideas.